2020
DOI: 10.1007/s11517-020-02280-z
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-acute EEG alterations predict functional and morphological outcomes in thrombolysis-treated ischemic stroke: a wireless EEG study

Abstract: Owing to the large inter-subject variability, early post-stroke prognosis is challenging, and objective biomarkers that can provide further prognostic information are still needed. The relation between quantitative EEG parameters in pre-thrombolysis hyper-acute phase and outcomes has still to be investigated. Hence, possible correlations between early EEG biomarkers, measured on bedside wireless EEG, and short-term/long-term functional and morphological outcomes were investigated in thrombolysis-treated stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
1
18
0
1
Order By: Relevance
“…31 These results are in line with a previous study in which a correlation between early EEG alterations and neurological deficit at admission, as well as a correlation between EEG changes and clinical outcome were observed. 3 A recent study reported the positive correlation between CTP hypoperfused volume and NIHSS. 19 EEG alterations, especially in terms of DAR, DTBAR and relative alpha parameters extracted in sub-acute phase were related to functional outcome.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…31 These results are in line with a previous study in which a correlation between early EEG alterations and neurological deficit at admission, as well as a correlation between EEG changes and clinical outcome were observed. 3 A recent study reported the positive correlation between CTP hypoperfused volume and NIHSS. 19 EEG alterations, especially in terms of DAR, DTBAR and relative alpha parameters extracted in sub-acute phase were related to functional outcome.…”
Section: Discussionmentioning
confidence: 97%
“…Encephalogram (EEG) could be applicable for bedside functional monitoring in emergency setting. 3 , 38 , 41 EEG is a non-invasive technique, characterized by high temporal resolution and it enables fast evaluation of instantaneous brain function. Moreover, it shows good sensitivity to acute changes in cerebral blood flow (CBF) 35 , 36 and neural metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing research interest towards the neurophysiological biomarkers for monitoring the progression of neurological disability usually measured by clinical scales [9][10][11][12][13][14]. Currently, there are no reliable objective biomarkers for disease progression in PD [9].…”
Section: Introductionmentioning
confidence: 99%
“…Two papers 33,34 that examined the same sample of subjects were treated as a single paper in the analysis. Nine papers [33][34][35][36][37][38][39][40][41] reported EEG and/or outcome measure scores at 2 or more time points. Therefore, we included data at each timepoint.…”
Section: Meta-analysis Methodsmentioning
confidence: 99%
“…EEG was obtained for both clinical [58][59][60][61][62][63][64][65] (n = 8 papers) and research [33][34][35][36][37][38][39][40][41][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] (n = 67 papers) purposes. Of 63 papers with mean EEG time ≤2 months post-stroke, 47 papers obtained EEG during rest, 1 paper obtained EEG during upper limb movement, and 15 papers obtained EEG response to stimuli, the majority being electrical nerve stimulation in 9 papers (Figure 3).…”
Section: Eeg Protocolmentioning
confidence: 99%